Prognostic model for tooth survival in patients treated for periodontitis - Clo´ vis M. Faggion Jr (Blackwell Synergy, 2007)
Background: In patients with periodontitis, a quantitative prognostic assessment is needed in order to make evidence-based decisions about retaining teeth or extracting and replacing them with a dental prosthesis. Methods: One hundred and ninety eight patients receiving active periodontal treatment in 1989 or 1990 and complying with supportive periodontal therapy (SPT) over an average of 11.8 2.3 years were included in the study. A generalized linear model was established and fitted via generalized estimating equations to identify predictors for tooth loss during SPT. Results: Of the 4559 teeth present at baseline, 166 (3.6%) were extracted during active treatment and 249 (5.5%) during SPT. Baseline findings of diabetes mellitus (OR54.17), reduced alveolar bone levels (OR51.04 for each 1% increment), increased tooth mobility (III versus 0: OR55.52), multiple roots (OR51.82), and non-vital pulp (OR52.24) were significant (po0.05) predictors for tooth loss during SPT. Based on these parameters, a prognostic model was constructed that provides estimates of tooth survival probability when periodontal therapy is rendered. Conclusion: Using a multivariate approach, a prognostic model was developed that may be of value for clinical decision making.